2022
DOI: 10.1111/jfbc.14121
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization and antioxidant activity of carboxymethylated polysaccharide from Pholiota nameko

Abstract: Studies have shown that free radicals are directly or indirectly associated with diseases, such as Alzheimer's (Carmen et al., 2019), liver injury (Qi et al., 2005), inflammation (Lyhatskyy & Fira, 2017), and cancer (Poillet-Perez et al., 2015). Reactive oxygen species (ROS), including hydrogen peroxide, hydroxy, and superoxygen anion radicals, play an important role in the regulation of cellular signal transduction pathways and the maintenance of homeostatic balance in humans. When the human body is stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Carboxymethylation is a common modification method of polysaccharides, which can improve the biological activity of polysaccharides. Zhang et al (2022) reported compared with unmodified polysaccharides, carboxymethyl polysaccharide of Pholiota nameko (CPPN) had significant antioxidant factor experiment revealed that the optimal CMLRP synthesis conditions established using RSM were a reaction duration of 2.22 h, the chloroacetic acid dosage is 2.02 g, and a temperature of 46.87 °C. Under these conditions, the predicted degree of substitution (DS) was determined to be 0.5101.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxymethylation is a common modification method of polysaccharides, which can improve the biological activity of polysaccharides. Zhang et al (2022) reported compared with unmodified polysaccharides, carboxymethyl polysaccharide of Pholiota nameko (CPPN) had significant antioxidant factor experiment revealed that the optimal CMLRP synthesis conditions established using RSM were a reaction duration of 2.22 h, the chloroacetic acid dosage is 2.02 g, and a temperature of 46.87 °C. Under these conditions, the predicted degree of substitution (DS) was determined to be 0.5101.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported the carboxymethylated cushaw polysaccharide had better ability to scavenge superoxide anions and hydroxyl radicals (Liu & Huang, 2019). And carboxymethyl polysaccharide had significant water solubility significantly (Chakka & Zhou, 2020;Zhang et al, 2022b). Also Phosphorylated polysaccharides improved the physicochemical properties of native polysaccharides and enhanced their biological activity, or even imparting novel biological activity (Xia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the standard molecular modification methods for polysaccharides include carboxymethylation, phosphorylation, sulfonation, sulfation, and alkylation. Which enhanced the antioxidant activity and water solubility of native polysaccharides significantly, and also provided structural diversity and even the addition of new bioactivities (Ahmad, 2021;Chakka & Zhou, 2020;Xie et al, 2020;Zhang et al, 2022a;Zhang et al, 2022b). Carboxymethylation is a widely studied modification method for many polysaccharides due to its advantages, such as low cost of reagents, simple operation, safe conversion, and low toxic or nontoxic reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…ABTS [2,2′-Azinobis-(3-ethylbenzthiazoline-6-sulphonate)] radical removal rate was determined as previously reported methods with minor modifications ( 39 ). The ABTS premix prepared from 10 mL of 2.4 mmol/L ABTS and 10 mL of 7 mmol/L potassium persulfate was kept in dark room for 12 h. The ABTS reaction solution was prepared by diluting the premixed solution with water to the absorbance of 0.700 ± 0.02 at 734 nm.…”
Section: Methodsmentioning
confidence: 99%